The Success of Online Passport Queue Registration Applications Using Delone and Mclean Models - Ramos, Ivan; Noor Yuliati, Lilik; Simanjuntak, Megawati (Jurnal Aplikasi Bisnis dan Manajemen, 2022)
Advancement in sophisticated information technology can be used for innovation in access to public services. In this study, the public service studied was the Online Passport Queue Registration Application (APAPO) at the Class I Non-TPI Bogor Immigration Office. This study aims to analyze the effect of system quality, information quality, service quality, user characteristics, usage rate, user satisfaction on net benefits APAPO using DeLone and McLean and find out the priority factors for improvement using the Important-Performance Analysis (IPA) method. The sampling technique used was convenience sampling where the sample was people who had applied for a passport using APAPO at the Immigration Office Class I Non TPI Bogor taken as many as 200 respondents with data collection using an online google form questionnaire, and then analyzed using the SEM method. The results of this study indicate that the quality of the system has no significant effect on usage and user satisfaction. The quality of information has no significant effect on usage and user satisfaction. Service quality has a significant effect on usage and has no significant effect on user satisfaction. User characteristics have a significant effect on usage. Usage has a significant effect on user satisfaction and net benefits. And user satisfaction has a significant effect on net benefits. From the results of the IPA analysis, system integration, format of output and assurance are indicators that services need to be improved. Keywords: DeLone and Mclean Model, APAPO, IPA, SEM, Bogor Immigration Office